The mortgage market in Egypt: barriers and recommendations to availability of housing finance - Mostafa, Mona (AUC Knowledge Fountain, 2012)
The Egyptian housing sector suffers from a number of deficiencies. Among these is the lack of an efficient housing finance mechanism. The mortgage market, formally developed in 2001, is still at nascent stages and is unable to provide such a mechanism for a large majority of would-be or actual buyers. This study examines the reasons behind the failure of the mortgage market to grow and thrive. It presents a qualitative analysis based on extensive interviews with the players in the mortgage market, including regulators, lenders and real-estate developers. It assesses the current market standing and identifies the barriers to the mortgage market and recommendations to overcome those barriers. Institutional immaturity and security measures are addressed at the core of problem as possible hypotheses to answer why mortgages are not more widespread. Through the intensive interviews, it is learned that there are specific barriers to mortgages as a housing finance mechanism. These barriers include, but are not limited to, the infrastructure associated with legal documentation and property registration; minimal mortgage education; hindrance in foreclosure policy and procedure; lack of an institutional leader; a limited secondary market; and an overall underexposure of Egyptian culture to mortgages. Market players participating in research offer recommendations that would improve the state of the mortgage market and overcome some of the barriers. Recommendations include nationwide awareness efforts, possibly starting with basic financial education at the school level; more promotion by regulators of the mortgage market; creation of mortgage-specific notaries; standardization of mortgage documents; and market synchronization through the establishment of a single national mortgage agency. This research demonstrates the importance of policy that is harmonious with existing supply of a commodity, in this case, housing, and the associated infrastructure.